Producción y realización del cortometraje Marcela - Jacob Camaiora, Giancarlo (2020)
The following paper is an analysis from the optics of direction and production, about the realization of the short film Marcela, cinematic piece that has as a central theme the election of which career to pursuit. The following aspects will be taken in account for the analysis: the objectives, the investigation period, development and execution, as well as the final results obtained and the lessons learned by the authors throughout the process. The following areas of interest will be covered in this paper: acting direction, art direction, cinematography, editing, colorization, sound editing, sound mixing and sound score. This project will try to answer how a short film, that participated in the most important peruvian film festival, was made.